Enhanced autophagy alleviated corneal allograft rejection via inhibiting NLRP3 inflammasome activity. Issue 5 (15th February 2022) - Wei, Chao; Ma, Li; Xiang, Demeng; Huang, Cixin; Wang, Huijin; Wang, Xin; Zhang, Sai; Qi, Xiaolin; Shi, Weiyun; Gao, Hua
Abstract : Autophagy has been reported to be involved in many aspects of innate and adaptive immunity. Manipulating autophagy is recognized as a promising therapeutic approach for treating immunological diseases, including allograft rejection, and graft‐versus‐host disease. However, whether autophagy was closely associated with the pathogenesis of corneal allograft rejection remains largely unknown. Here, we showed that rapamycin (RAPA)‐induced autophagy alleviated corneal allograft rejection. By contrast, blocking autophagic activity using 3‐methyladeine (3‐MA) aggravated corneal transplantation rejection. Mechanistically, we revealed that the enhanced autophagic turnover by RAPA inhibited NLRP3 inflammasome activity through NLRP3 degradation. While blocking the fusion of autophagosomes with lysosomes by bafilomycin A1(BafA1), the reduced NLRP3 inflammasome activity induced by RAPA was significantly restored, with increased protein levels of NLRP3 and cleaved Casp‐1(p10), as well as IL‐1β secretion. Moreover, we further revealed that pharmacologically blocking NLRP3 inflammasome signaling prolonged the survival of corneal allografts. Taken together, these findings underscored the critical roles of enhanced autophagy in treating corneal allograft rejection, which provided an alternative intervention strategy to control corneal transplantation rejection. Abstract : Increased autophagic activity reduces corneal allograft rejection by blocking NLRP3 inflammasome.